2023
DOI: 10.3390/pharmaceutics15071874
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Paclitaxel-Loaded ZIF-8 Metal-Organic Framework Nanoparticles Modified with Peptide Dimers and an Evaluation of Its Inhibitory Effect against Prostate Cancer Cells

Abstract: Prostate cancer (PC) is one of the common malignant tumors of the male genitourinary system. Here, we constructed PTX@ZIF-8, which is a metal-organic-framework-encapsulated drug delivery nanoparticle with paclitaxel (PTX) as a model drug, and further modified the synthesized peptide dimer (Di-PEG2000-COOH) onto the surface of PTX@ZIF-8 to prepare a nanotargeted drug delivery system (Di-PEG@PTX@ZIF-8) for the treatment of prostate cancer. This study investigated the morphology, particle size distribution, zeta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This is because the lipid monolayer coating of nanoparticles increased the cell membrane interaction with time . Zhao et al reported courmarin-6-loaded Di-PEG-ZIF nanoparticles showed 1.8-fold cellular uptake in Lncap cells in 2 h of study . For our proposed system, it could be possible that nanocarriers were internalized through the endocytosis process, in which the nanoparticles initially stayed in the cytoplasm before lysozyme is released and traveled to the nuclear or perinuclear region .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This is because the lipid monolayer coating of nanoparticles increased the cell membrane interaction with time . Zhao et al reported courmarin-6-loaded Di-PEG-ZIF nanoparticles showed 1.8-fold cellular uptake in Lncap cells in 2 h of study . For our proposed system, it could be possible that nanocarriers were internalized through the endocytosis process, in which the nanoparticles initially stayed in the cytoplasm before lysozyme is released and traveled to the nuclear or perinuclear region .…”
Section: Resultsmentioning
confidence: 93%
“…107 Zhao et al reported courmarin-6loaded Di-PEG-ZIF nanoparticles showed 1.8-fold cellular uptake in Lncap cells in 2 h of study. 108 For our proposed system, it could be possible that nanocarriers were internalized through the endocytosis process, in which the nanoparticles initially stayed in the cytoplasm before lysozyme is released and traveled to the nuclear or perinuclear region. 109 we also observed colocalization of intracellular fluorescence after 24 h, which could indicate undissociated protein and polymer particles.…”
Section: Cytotoxicity Study Of Protein-encapsulated Nanoparticlesmentioning
confidence: 99%
“…Zhao et al have developed a cancer-targeting system using MOF and di-peptides [63]. MOF, a nanocarrier, is a porous material synthesized using a coordination bond between a metal ion and an organic linker and has the advantages of adjustable porosity and structure, high surface area, and the ability to load various drugs [64][65][66][67].…”
Section: Receptor-mediated Peptidementioning
confidence: 99%
“…Talking about imidazole acceptability in other chemical biology-oriented approaches, it has shown tremendous potential. These include serving as pH-responsive potent antimicrobials [ 164 ], improving the photophysical characteristics of azo dyes [ 165 , 166 , 167 ], decreasing side toxicities [ 13 , 168 , 169 , 170 ], and successful chemical integration in polymeric materials as theragnostic applications (such as in zeolitic imidazolate framework applications in drug delivery) [ 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 ].…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%